Effect of innovative bioproducts on the performance of bioformulated earthen plasters. (29th March 2021) - Parracha, J.L.; Pereira, A.S.; Velez da Silva, R.; Silva, V.; Faria, P.
Highlights: Earth mortars are ecological but vulnerable to water, limiting their applicability. New nontoxic bioproducts were developed and used for earth mortars' bioformulation. An air entraining effect occurred in the fresh state, increasing mortarś porosity. A negative decrease on mortars mechanical performance was obtained. A positive decrease on both thermal conductivity and vulnerability to water of mortars was achieved. Abstract: Biotechnologies mainly based on precipitation of chemical compounds produced by microbial metabolism can be used as biotreatment or bioformulation of construction materials. Bioformulation of cement-based materials has been a common research practice, though its application to earthen-based building materials is still limited. Although earth mortars are vulnerable to water damage, they are nowadays often used as plasters on new constructions but also for the retrofitting of existent buildings. Their reversibility and compatibility with old substrates make them also interesting for conservation interventions, namely when applied to protect archaeological structures as sacrificial renders. In this study, an innovative bioproduct based on cellular extracts of Escherichia coli, cultured in Lysogeny broth (LB) medium and supplemented with iron, was developed and used as a component for earth mortars' bioformulation. The Escherichia coli strain used is classified as not hazardous. An additional earth mortar bioformulated with LB medium as mixing liquid was also tested to assess the influence of the culture medium. The iron supplement was chosen to infer about iron oxide biomineral formation, a less toxic mineral than calcite, since no toxic by-products are produced, and iron oxide minerals have a longer lifetime when compared with calcite crystals. Bioformulated mortars presented a very distinct porous structure, with a significant decrease on mechanical properties. Nevertheless, they also showed a decrease on thermal conductivity, a slight consolidative effect, and a significant decrease on vulnerability towards water. Apart from the possible use as mortar air entraining agents, the obtained results show the interest on further studies on the use of nontoxic iron-based bioproducts for earthen mortars optimization.